Restitution for mistaken payments: Whither mistakes of law? - Perham, Benjamin (Victoria University of Wellington Law Review, 1995)
The traditional rule at common law precluded restitution for payments made by mistake where the payer's mistake had been one of law. That rule was set aside in New Zealand in 1958. Other jurisdictions are likely soon to follow. This article considers the law of mistaken payments absent the traditional rule. Assuming restitution is available for mistakes of law, ought the payer's ability to recover nevertheless differ according to whether the mistake was one of law or one of fact? The thesis of this article is that an approach to mistaken payment cases that deals directly with the competing merits of the parties and the relevant policy concerns removes any need to distinguish between the two types of mistake. A distinction between mistakes of law and mistakes of fact should be irrelevant to the payer's ability to recover.